RACK1 (receptor for activated C‐kinase 1) interactions with spectrin repeat elements. Issue 1 (23rd December 2014) - Myklebust, Line M.; Horvli, Ole; Raae, Arnt J.
Abstract : Receptor for activated C‐kinase 1 (RACK1) is an intracellular scaffolding protein involved in a multitude of signalling pathways. The cytoskeleton is fundamental for intracellular cell signalling as it forms an interconnected network of regulatory proteins. Here, spectrin is a central component as it forms the actin–spectrin network that serves as docking surfaces for cellular components. The interaction between RACK1 and components of spectrin, the single spectrin repeats R16, R17 and the double spectrin repeat R1617 from the α ‐spectrin chain were investigated by biosensor technology and docking analysis. RACK1 associated only weakly to R16 ( K D  = 1.0 ± 0.5 × 10 −6  M), about 20 times stronger to R1617 ( K D  = 5.3 ± 0.7 × 10 −8  M) and 100 times stronger to R17 ( K D  = 0.9 ± 0.3 × 10 −8  M). Docking analysis showed that while R16 alone preferentially docked with its B‐helix, R17 docked through its A‐helix and BC loop. The double repeat and RACK1 mainly formed two different complex conformations. R1617 docked tangentially to the N/C‐terminal of RACK1 or radially along a groove on the outer surface of RACK1. These configurations could account for the slight increase in entropic and the decrease in enthalpic interactions for the R1617–RACK1 interaction, compared with the interactions of RACK1 to the two single repeats. Our results suggest a mode of interaction that allows spectrin to attach to the N/C part of RACK through the inter‐helical AB and BC loops and adopt a multitude of configurations in between the two limiting configurations. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : We present detailed surface plasmon resonance (SPR)‐based binding kinetic data and thermodynamic analysis of the interactions between the scaffold protein receptor for activated C‐kinase 1 (RACK1) and components of the α ‐spectrin chain. Our data show that the single spectrin repeat R16 associated weakly to RACK1 ( K D  = 10 −6  M) whereas the double repeat R1617 and R17 bound about 20 and 100 times stronger to RACK1, respectively. Thermodynamic analysis of the R1617 interaction with RACK1 demonstrated a prominent enthalpic component through the BC‐loop of R17 and a possible entropic contribution from R16. Docking analysis indicated a mode of interaction where spectrin attaches to the N/C‐section of RACK through the inter‐helical AB and BC loops. Our results suggest a model for the RACK1 association in the cytoskeleton/membrane system.